Measuring the effect of forced irrigation on the front surface of PV panels for warm tropical conditions. (November 2019) - Osma-Pinto, German; Ordóñez-Plata, Gabriel
Abstract: Irrigating the front surface of a PV panel is one method for reducing its operating temperature, thus increasing the output power. Several studies have investigated this method. Nevertheless, information on the thermal effects and energy benefits provided by irrigation over several operating cycles and water flow rates in warm-tropical conditions is lacking. Thus, this work presents the experimental characterization of the operating temperature and output power from irrigated 255 W PV panels. The experiment considered twelve irrigation regimens with four flow rates (1.75 l/min, 3.75 l/min, 4.75 l/min, and 9.50 l/min) and four operating cycles (1':29', 5':25', 15':15', and continuous). The study provides a description of transient cooling processes as functions of flow rate and solar irradiation, as well as heating of the PV panel. Such description is based on data analysis using two indices: relative temperature difference (RTD) and generated power increase (GPI), which quantifies the additional generated energy and estimates the net energy benefit considering the energy consumed by the irrigation system. Results indicate that irrigation can enhance daily energy production by 10%; a flow rate equal to or greater than 3.75 l/ min (2.34 l/min/m 2 ) produces similar effects. The GPI caused by irrigation depends on the solar irradiation, where GPI is found to be 0.5% to 2.0% for 400 W/m 2 or lower, 2% to 5% for values between 400 W/m 2 and 800 W/m 2, and 5% to 10% for 800 W/m 2 or greater. The power consumed by the irrigation system significantly affects the net energy benefit. Highlights: An irrigated PV panel can experiment direct and indirect cooling, and heating. Irrigating is attractive only for values of solar irradiation greater than 500 W/m 2 . Irrigating can increase up to 10% of the daily energy generation of a PV panel. Energy benefit by irrigation depends strongly on irrigation time and power of pump. Discontinuous irrigation cycles can be more viable than continuous irrigation.